Metodos de lucha quimica para el control del zabro del cereal, Zabrus tenebrioides (Goeze, 1777)(Col.: Carabidae) en Navarra - Tiebas, M.A.=700 1 Biurrun, R.; Esparza, M.J.
(En, Es)
ilus., 12 ref.
Keywords: ZABRUS; CEREALES; CEBADA; CONTROL QUIMICO; INSECTICIDAS; CLORPIRIFOS; MALATION; TRICLORFON; ESPAÑA